1997
DOI: 10.1097/00006534-199702000-00041
|View full text |Cite
|
Sign up to set email alerts
|

Total Lower Lip Reconstruction with a Sensate Composite Radial Forearm-Palmaris Longus Free Flap and a Tongue Flap

Abstract: The technique of total lower lip reconstruction with a composite radial forearm-palmaris longus free flap was further refined in this report. A ventral tongue flap enhanced the lip aesthetics by recreating the vermilion. Lip suspension was enhanced by securing the palmaris tendon to the malar eminences as well as to the cut ends of the orbicularis oris muscle. The patient achieved oral continence as well as dynamic movement of the lip during speaking and swallowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 5 publications
0
43
0
Order By: Relevance
“…Advantages of this flap are good color texture match, glabrousness, ease of dissection, great length, and large diameter of the vascular pedicle and the possibility of becoming a sensate flap. 6 Disadvantages include small skin paddle, sacrifice of one of two major arteries of the hand, donor site scar, and the risk of tendon exposure. Thus, Jeng and colleagues 4 and Serkan and others 1 reported that the composite anterolateral thightensor fasciae latae flap could be a good alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of this flap are good color texture match, glabrousness, ease of dissection, great length, and large diameter of the vascular pedicle and the possibility of becoming a sensate flap. 6 Disadvantages include small skin paddle, sacrifice of one of two major arteries of the hand, donor site scar, and the risk of tendon exposure. Thus, Jeng and colleagues 4 and Serkan and others 1 reported that the composite anterolateral thightensor fasciae latae flap could be a good alternative.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques can be categorized as static or dynamic procedures. 1,4,8 Methods of static suspension include use of muscles or a fascia sling anchored permanently to the nasolabial area, 3 periosteum of the zygomatic eminences, 6,13 or bilateral modiolus. 4,7 The major disadvantage of this suspension is sialorrhea when speaking or eating.…”
Section: Discussionmentioning
confidence: 99%
“…The free radial forearm flap, originally described by Song [18], was used by Sadove [16] and Serletti [17] in reconstruction of the lower lip after resection of malignant tumours. It has one of the longest available vascular pedicles, thus the microsurgical anastomoses can be performed far away from the infected and fibrosed tissues, preferentially in the neck area.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation the defects in the perioral and midface region were reconstructed with the free radial forearm flap. This flap has been used successfully in oral and facial reconstruction after tumour resection [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Traditional reconstructive procedures in the head and neck region include combinations of skin grafting, local flaps, tissue expansion, prefabrication, and free tissue transfers. [4][5][6][7][8][9][10][11][12][13][14] However, the cosmetic outcome of these creative surgical procedures has not proved satisfactory in long-term follow-up because they quite often result in a mask-like appearance that lacks normal facial movement and expression. Furthermore, the patients who undergo this surgery are often subjected to multiple procedures, the aim of which is to optimally improve the appearance and function of the face.…”
mentioning
confidence: 99%